ナンキョク ヒョウショウ,シラセ リュウイキ エンガン ニ オケル ヒョウメン ケイタイ ノ クウチュウ シャシン ハンドク ト コオリ ノ リュウシュツ リョウ ノ スイテイ - 藤井, 理行; フジイ, ヨシユキ; Fujii, Yoshiyuki (1981)
P(論文) 1962年, 1969年, 1975年および1977年に撮影された空中写真の解析をもとに, 白瀬氷河氷舌部の特徴的な表面構造と, 斜面下降風系について述べ, また白瀬流域からの流出量を, 氷舌部での流動量と氷厚が異なる3つの副流域に分け, 算定した。氷の流動速度は, 氷山の移動量から求め, 白瀬氷河氷舌部については, 平均で2500m・a^<-1>, 白瀬氷河西側のsheet flowについては, 360m・a^<-1>の値を得た。Calving front付近での氷山の厚さは, 2級図化機を用いての空中写真測量による氷山高から求めた。これらの値から, 白瀬流域からの氷の流出量として, 13.4～14.7×10^9t・a^<-1>を得た。また, 白瀬流域の過去数年間の質量収支として, これまでに報告された流入量との差から, -0.7～-2.0×10^9t・a^<-1>を得た。 Aerophotographs taken by the Japanese Antarctic Research Expedition in 1962,1969,1975 and 1977 are analyzed to classify distinctive surface structures, katabatic wind regime at the terminus of the Shirase Glacier (70°S, 39°E), and ice discharge from the Shirase drainage basin is calculated as the sum of ice discharge from three subdivisional drainages with different flow velocities and ice thickness at their outlets. From the displacement of icebergs, the flow velocities of about 2500m・a^<-1> and about 360m・a^<-1> are obtained for the Shirase Glacier and the sheet flow in the west of the Shirase Glacier, respectively. Thicknesses of the icebergs near calving front are also obtained by the aerophotogrammetry. The total discharge from the Shirase drainage basin, 13.4 to 14.7×10^9t・a^<-1>, is reported to be more accurate than the values by other authors. Substracting the total discharge from the income previously reported by the other authors, the mass budget of the ice sheet in the basin is estimated to be -0.7 to -2.0×10^9t・a^<-1> during the last several years. departmental bulletin paper